Multifunctional coatings to simultaneously promote osseointegration and prevent infection of orthopaedic implants - Raphel, Jordan; Holodniy, Mark; Goodman, Stuart B.; Heilshorn, Sarah C. (Biomaterials, 2016)
The two leading causes of failure for joint arthroplasty prostheses are aseptic loosening and periprosthetic joint infection. With the number of primary and revision joint replacement surgeries on the rise, strategies to mitigate these failure modes have become increasingly important. Much of the recent work in this field has focused on the design of coatings either to prevent infection while ignoring bone mineralization or vice versa, to promote osseointegration while ignoring microbial susceptibility. However, both coating functions are required to achieve long-term success of the implant; therefore, these two modalities must be evaluated in parallel during the development of new orthopaedic coating strategies. In this review, we discuss recent progress and future directions for the design of multifunctional orthopaedic coatings that can inhibit microbial cells while still promoting osseointegration.